2018
DOI: 10.1080/09537325.2018.1550254
|View full text |Cite
|
Sign up to set email alerts
|

A framework of disruptive sustainable innovation: an example of the Finnish food system

Abstract: A framework of disruptive sustainable innovation: an example of the Finnish food system Disruptive innovations are perceived necessary for accelerating sustainability transitions. However, it is not always clear what exactly is meant by it, what is to be disrupted, and by whom. Socio-technical transition research on pays too much attention at the technological niche-innovations in the production, and overlooks business model innovation and user practices in the consumption, whilst management literature on disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Governments often aim financial support at incumbent industries with high employment, such as car manufacturers, airlines, and oil companies. We suggest that recovery funds could rather target financial support towards forward-looking objectives, supporting innovative technology that could mitigate climate warming and biodiversity loss (Wilson 2018 ; Kuokkanen et al 2019 ). Accounting of the global recovery funds shows that even a fraction of the investments, if directed to the development of sustainable energy, could be sufficient to meet the Paris Agreement objectives (Andrijevic et al 2020 ).…”
Section: Moving Towards a Sustainable Future Pathmentioning
confidence: 99%
“…Governments often aim financial support at incumbent industries with high employment, such as car manufacturers, airlines, and oil companies. We suggest that recovery funds could rather target financial support towards forward-looking objectives, supporting innovative technology that could mitigate climate warming and biodiversity loss (Wilson 2018 ; Kuokkanen et al 2019 ). Accounting of the global recovery funds shows that even a fraction of the investments, if directed to the development of sustainable energy, could be sufficient to meet the Paris Agreement objectives (Andrijevic et al 2020 ).…”
Section: Moving Towards a Sustainable Future Pathmentioning
confidence: 99%
“…However, despite the effort to include a range of factors reflecting the complexity associated with RIC, there is still room for advancement, especially in association with the "dynamic-context" of this concept. Grounded on Schumpeter's theory of disruptive innovation, the process of technological innovation is always dynamic and nonlinear [29]. Hence, the determinants of RIC may show different effects at different states of innovation capacity.…”
Section: Measurements and Determinants Of Regional Innovation Capacitymentioning
confidence: 99%
“…The existing literature on innovation capacity research has mostly used static empirical methods, such as fixed effect stochastic frontier, and spatial econometric models [6,11,27], based on cross-national or cross-regional comparisons of innovation capacity at a fixed period [17,19,28]. Technological innovation is an inherently dynamic and nonlinear process over time [29]. Blundell et al [30] indicated that the transition process of innovation capacity cannot be comprehensively explained in a linear trajectory, so its modeling and measurements should integrate the analysis of dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kuokkanen et al (2018) In order to respect spatial differences in sustainability challenges, Boons et al (2013) make a clear distinction between developed consumerist economies, emerging economies and so called Base-of-the-Pyramid economies. Developing sustainable protein systems is a challenge especially for developed consumerist economies due to an inherently inefficient conversion of meat protein production from feed to food (de Boer et al, 2006).…”
Section: Sustainable Protein System Innovations and Entrepreneurshipmentioning
confidence: 99%
“…Developing sustainable protein systems is a challenge especially for developed consumerist economies due to an inherently inefficient conversion of meat protein production from feed to food (de Boer et al, 2006). Alternative protein products can be presented as disruptive sustainable innovations (Kuokkanen et al, 2018), which aim to reduce meat protein intake (Aiking, 2014) and to replace meat proteins with plant, mushroom and algae protein products. In addition, sustainable innovations could aim to increase the diversity of animal-based proteins by shifting towards underutilized fish species and insects.…”
Section: Sustainable Protein System Innovations and Entrepreneurshipmentioning
confidence: 99%